THE EFFECTIVENESS OF THE MENTORING METHOD IN SUPPORTING SCHOOL INSPECTORS TO IMPROVE THE PEDAGOGICAL COMPETENCE OF EARLY CHILDHOOD EDUCATION TEACHERS IN JAMBU SUBDISTRICT, SEMARANG REGENCY - Ekawati Indrianingsih; Tri Suminar (SOSIOEDUKASI, 2026)
This study examined the effectiveness of a mentoring-based professional development model in improving the pedagogical competence of early childhood education (PAUD) teachers compared with conventional supervision. A quantitative approach employing a quasi-experimental pre-test–post-test nonequivalent control group design was conducted involving 60 teachers equally assigned to experimental and control groups. The experimental group participated in a structured mentoring program emphasizing collaborative reflection, classroom observation, constructive feedback, and continuous professional support, whereas the control group received conventional workshop-based supervision. Data were collected using a validated and reliable pedagogical competence instrument and analyzed using descriptive statistics, paired-sample t-tests, and normalized gain (N-gain) analysis. The results showed statistically significant improvements in both groups (p < 0.001); however, the experimental group demonstrated substantially greater improvement, with the mean score increasing from 65.18 to 88.19, compared with 64.93 to 75.52 in the control group. The experimental group also achieved a moderate N-gain score of 0.66, indicating meaningful improvement in pedagogical competence. These findings suggest that structured mentoring provides a more effective approach than conventional supervision for strengthening teachers' pedagogical competence. The results support the integration of mentoring into continuous professional development programs for PAUD teachers and provide practical evidence for supervisors, school leaders, and educational policymakers in improving the quality of teacher supervision.